Kiai vis a vis Media Logic: Revisiting the Power of Internet and Kiai in Pandalungan Muslim Community - Fazlul Rahman (Kawalu: Journal of Local Culture, 2017)
Abstract Internet becomes an integral part of current Indonesian society‘s life. Meanwhile, the figure of kiai clearly cannot be separated from the history of Indonesian socio-religious life up until recently. Both the kiai and Internet are inseparable parts of current Indonesian social reality, in which, each of them possessed their particular share of power and ran according their own logics. Focusing on the case of Pandalungan Muslims community, where the kiai‘s authority is greatly acknowledged, this paper will shed the lights on the logic behind those two powers and the contestation (for authority) occurred between them. This paper concludes that the logic of the kiai-ness is the logic of culture and media logic is in the logic of culture. This made the kiais‘ authority is still standing strong in current media life.